Rekonstruksi Budaya Organisasi: Korupsi di Indonesia Sangat Mengkhawatirkan, Termasuk di BUMN - Rabbina, Hammi Nikma; Santoso, Oktavia Artikawati; Wahjono, Sentot Imam (Innovative: Journal Of Social Science Research, 2025)
Corruption within Indonesia's BUMN remains a significant challenge despite various anti-corruption policies being implemented. According to the Corruption Eradication Commission (KPK), from 2004 to 2024, 181 corruption cases involved BUMN, with 38 cases occurring in 2024 alone. Major cases involving PT Timah, Pertamina, Asabri, Jiwasraya, and Garuda Indonesia have resulted in state losses reaching hundreds of trillions of rupiahs. Although policies such as Good Corporate Governance (GCG), a whistleblowing system (WBS), and gratuity control mechanisms have been introduced, their effectiveness remains questionable. The window-dressing phenomenon has made these strategies appear effective on the surface but fail to address the root problems. One of the primary causes of corruption in BUMN is a weak organizational culture. To address this issue, a comprehensive cultural transformation is needed, emphasizing the reinforcement of a strong culture of shame and stricter oversight mechanisms. A well-established culture of shame will create collective awareness that corruption is a disgraceful act harming the nation. Furthermore, implementing fraud control measures and enhancing transparency is expected to reduce corruption practices in BUMN. With a stronger cultural reform, BUMN can function more effectively as national economic drivers while increasing their global competitiveness.